Functional Protective Effects of Long-Term Memantine Treatment in the DBA/2J Mouse. - Atorf, Jenny; Scholz, Michael; Garreis, Fabian; Lehmann, Julia; Bräuer, Lars; Kremers, Jan (Documenta Ophthalmologica, 2013)
Purpose: To analyse the effects of long-term memantine treatment on the retinal physiology and morphology of DBA/2J mice. Methods: DBA/2J (D2J) mice received i.p. injections of the NMDA receptor antagonist memantine, which protects neurons from abnormally elevated glutamate levels, twice a day over a period of 7 months. At the age of 2, 6 and 10 months, the intraocular pressure (IOP) and electroretinograms (ERGs) were measured in all treated D2J mice, in untreated D2J controls and in C57Bl/6 (B6) wild-type mice. After the last measurement at the age of 10 months, the mice were killed and the retinae and the optic nerves were analysed morphologically. Results: The IOP increased with age in both D2J and B6 mice with a larger increase in the D2J strain. IOPs were not influenced by memantine treatment. The response amplitude of the scotopic flash ERG decreased with age in the D2J strain. This amplitude decrease, particularly that of the b-wave, was smaller in treated D2J mice. The retinae of treated D2J mice exhibited less peripheral degeneration of cone photoreceptors, and optic nerve neuropathy was less frequent. Conlcusions: Application of the NMDA receptor antagonist memantine diminished retinal neurodegeneration in the D2J mice and had a protective effect on the b-wave amplitude of the scotopic flash ERG. This protection may occur secondarily as memantine primarily acts on retinal ganglion cells. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.med.AI.LAIPDL.functi
Keywords: DBA/2J mouse; Electroretinography; Memantine; Neurodegeneration